2021
DOI: 10.7759/cureus.14313
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Intake and Mental Health in College Students

Abstract: Background The effect of caffeine on the human body, both short-term and long-term, has been studied in great depth, particularly its association with psychiatric disorders. This study aims to investigate whether there is a correlation between caffeine intake and anxiety and depression among college students. Methodology A survey was administered to college students at Florida State University. Data regarding participant characteristics and caffeine intake were collected. Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
(10 reference statements)
0
14
0
5
Order By: Relevance
“…Coffee seems to be a traditional “refreshing” method, and an earlier study shows that 79% of college students use caffeine to feel awake. 6 A study of student populations at the University of Florida linked caffeine consumption to depression and higher levels of anxiety among college students. However, the cause-effect relationship has not been undefined; another study of adults in Australia showed that coffee leads to a risk of sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee seems to be a traditional “refreshing” method, and an earlier study shows that 79% of college students use caffeine to feel awake. 6 A study of student populations at the University of Florida linked caffeine consumption to depression and higher levels of anxiety among college students. However, the cause-effect relationship has not been undefined; another study of adults in Australia showed that coffee leads to a risk of sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine is regularly consumed in many societies and is used to provide alertness and reduce drowsiness ( 26 , 45 ) . However, caffeine can be addictive, and withdrawal symptoms may occur when caffeine intake is stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Kendler et al [ 94 ] analyzed data from the Virginia Twin Registry of about 3600 adult twins and reported that the risk of developing anxiety increased after consumption of >6 cups of caffeinated coffee per day. Additionally, Bertasi et al [ 95 ], in their study among 114 college students, showed that high caffeine intake is associated with higher levels of anxiety. Botella et al [ 4 ] examined 3323 students (11–17 years old) and showed that the effect of caffeine on anxiety is significant mainly in boys—the anxiety increased with increased dose of caffeine intake.…”
Section: The Role Of Caffeine In Various Systems In the Human Bodymentioning
confidence: 99%